Lacrimal Gland Fistula following Severe Head Trauma - Cemil Demir; Ibrahim Toprak; Sukru Gungen; Alp Arslan (Case Reports in Medicine)
We aim to present a unique case with discharging lacrimal gland fistula secondary to severe head trauma by an animal. A 9-year-old girl presented with serous fluid discharge from a cutaneous fistula in the left orbital region. The patient had history of surgery for traumatic frontal bone fracture and skin laceration in the superior orbital rim three weeks earlier. She underwent a complete ophthalmological examination and there was no anterior segment or fundus pathology. The orifice of the fistula was detected in mediolateral part of the left superior orbital rim and fluid secretion was increasing with irritation of the left eye. Neurosurgical complications were excluded and radiological assessment was nonremarkable. The patient’s legal representatives were informed and lacrimal gland fistulectomy was planned. However, the fistula was self-closed one week after initial ophthalmological examination, and the patient had no symptoms. In conclusion, traumatic injuries of superior orbital region should be carefully evaluated and wounds should be well closed to prevent consecutive lacrimal gland fistula.